Multiple and multipolar Fano resonances in plasmonic nanoring pentamers - Liu, Hailong (2014)
The optical properties of plasmonic nanoring pentamers are experimentally and theoretically investigated in the near-infrared spectral region, where the nanoring metamolecules allow complex optical design by tuning a single geometrical parameter (the inner radius of the nanoring). Even in fully four-fold symmetric nanoring pentamers, unconventional plasmonic coupling paths generate multiple Fano resonances which would not appear in symmetric nanodisc oligomers. In addition, inhomogeneous elementary units in the pentamer induce additional resonances due to high-order dark modes, while complete breaking of the four-fold symmetry results in sharp multipolar Fano resonances upon the hybridization of dark and bright modes. This approach demonstrates a simple way to engineer plasmonic couplings by subtle changes of uniform metamaterial design.